Integration of program evaluation and review technique (PERT), gantt chart and genetic algorithm in project management scheduling - Ahmad, Siti Hasziani (2014)
Project scheduling is important to the completion of a project. Since having delay, out of inventory and budget overrun make the failure of the project, project managers shall be able to handle a project with a certain scheduling decision making tool accordingly. A good technique for scheduling the project is required such that a proper manageable schedule can be suggested. In this thesis, the discussion on the integration approach, which combines Program Evaluation and Review Technique (PERT), Gantt Chart (GC) and Genetic Algorithm (GA), is carried out. However, there are another techniques that have been considered before choosing that techniques which are Critical Path Method (CPM) and Work Breakdown Structure (WBS). The aims are (1) to review the existing scheduling techniques, (2) to propose an integrated approach for solving the scheduling problem in the construction industry, and (3) to compare the applicable of the approach proposed with the existing techniques. For doing so, three steps are taken into account. First, doing the integration of PERT and GC, where Earliest Start time (ES) and Earliest Finish time (EF) are calculated. Second, is applying GA to the existing integration approach. In GA procedure, the chromosome is generated randomly to obtain the gene of parents. Further from this, the gene of offspring is refined through the operators of crossover and mutation. Third, the diagram of GC is depicted. For illustration, a set of the real data obtained from a construction company is studied. The project is to build the bounding walls at four different roads in Pasir Gudang, Johor Bharu. By using the approach proposed, a comprehensive schedule is produced, where the finishing time of the project is six day earlier or 6.06% than the original finishing time, which is 99 days. In conclusion, the efficiency of the approach proposed is highly recommended for project managers in developing an effective schedule.